Hydractinia angusta Hartlaub 1904 - ÁLVARO L. PEÑA CANTERO (Zenodo, 2017)
? Hydractinia angusta Hartlaub, 1904 (*) Hydractinia angusta — Totton, 1930: 138; Cerrano et al. , 2000: 488–493, figs 2–5; 2001: 577–580; Peña Cantero et al. , 2013: 737–739, figs 3g –h, 4a–c. Remarks. See Peña Cantero (2015) for a re-description of this species and a wide discussion about it. The only reliable record for this species is from the Bellingshausen Sea (cf. Peña Cantero 2015). Other records, including those from the Ross Sea [i.e. from McMurdo Sound (Totton 1930) and Tethys Bay (Cerrano et al. 2000, 2001; Peña Cantero et al. 2013)], need confirmation. Published as part of ÁLVARO L. PEÑA CANTERO, 2017, Benthic hydroids (Cnidaria, Hydrozoa) from the Ross Sea (Antarctica) collected by the New Zealand Antarctic expedition BioRoss 2004 with RV Tangaroa, pp. 1-65 in Zootaxa 4293 (1) on page 16, DOI:10.11646/zootaxa.4293.1.1, http://zenodo.org/record/828475